Exploring the reforms in tuberculosis control program in India/Hindistan'daki yeni tüberküloz kontrol programı - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava; Jegadeesh Ramasamy (Turkish Society of Public Health Specialists, 2014)
Abstract The Global Tuberculosis Report - 2013 has revealed that in the year 2012, 11.6 million new cases of tuberculosis (TB) have been reported worldwide, of which India contributed to more than 25% of cases. Owing to the universal distribution, significant impact on the quality of life, and high associated fatality rates, TB in today's world is the biggest public health disease of an infectious nature. Since the launch of the Revised National TB Control Program (RNTCP), the program has been scaled-up and modified in different domains diagnostics, treatment, involvement of medical college and private sector, along with some innovative measures. To conclude, RNTCP is the most flexible program in the country and with the recent modifications in the program it has become even more accessible and user-friendly, thus progressing steadily towards achieving universal access to TB care. Key words:  Tuberculosis, Revised National Tuberculosis Control Program, public health, diagnosis, India Özet Küresel Tüberküloz Raporu-2013, 2012 yılında dünya genelinde 11.6 milyon yeni tüberküloz (TB) olgusunun raporlandığını -ki bu olguların %25'inden fazlasında Hindistan'ın payı bulunuyordu- gözler önüne serdi. Yaygın görülüşü, yaşam kalitesi üzerindeki anlamlı etkisi ve yüksek fatalite hızları ile ilişkisi nedeniyle TB günümüzde dünyanın enfeksiyon kaynaklı en büyük halk sağlığı sorunudur. Revize Ulusal TB Kontrol Programı (RUTKP) ilan edildikten bu yana büyüdü, tanı, ve tedavinin çeşitli alanları ile ilgili olarak modifiye edildi, tıp fakülteleri ve özel sektör sürece katıldı. Sonuç olarak RUTKP ülkedeki en esnek programdır ve programdaki güncel düzenlemelerle birlikte daha ulaşılabilir ve kullanıcı dostu hale gelmiştir. Bu nedenle programdaki ilerleme, evrensel TB bakımına erişinceye dek süreklidir.  Anahtar Kelimeler: Tüberküloz,  Revize Ulusal Tüberküloz Kontrol Programı, halk sağlığı, tanı, Hindistan